A Mogadishu-Budapest-Nairobi háromszög - Szilasi, Ildikó (Afrika Tanulmányok / Hungarian Journal of African Studies, 2008)
The ”Do not cry anymore Somalia!” programme supported by the African-Hungarian Union started in September 2008. An education and income generating centre called RAJO (Somali word, meaning hope) has opened on 10 September 2008. The beneficiaries of the project are especially those Somali asylum seekers in Nairobi, Kenya, whose family members are already recognized refugees in Hungary and whose family reunification case is already under process. The article shows the process of setting up a project from field assessment to implementation, from a personal point of view of those NGO representatives who have worked on this issue.